2019
DOI: 10.1891/1078-4535.25.4.e36
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Relationship-Based Care as a Professional Practice Model: Promoting Nurses ‘Understanding and Confidence to Apply in Practice

Abstract: Professional practice models (PPMs) guide nursing practice, professional behaviors, and clinical leadership. Health care continues to evolve (e.g., through health system mergers), and nurses may need to adopt and understand new PPMs to confidently align their interventions and professional nursing practice accordingly. The purpose of this project was to create an educational module about a new PPM based on the model of relationship-based care (RBC), which was adopted following a health system merger. The modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Schools of nursing and medicine need to prepare future practitioners to care for patients in a virtual health care environment, with competencies specific to these digital tools [92,95]. Fortunately, nursing theories [22,33,35] and conceptual models [96] exist to support this important work, and relationship-based care has been successfully incorporated into health care clinician curriculum and professional practice models [97,98], showing improvement in health care delivery [41,99,100].…”
Section: Implications For Practice Policy and Professional Developmentmentioning
confidence: 99%
“…Schools of nursing and medicine need to prepare future practitioners to care for patients in a virtual health care environment, with competencies specific to these digital tools [92,95]. Fortunately, nursing theories [22,33,35] and conceptual models [96] exist to support this important work, and relationship-based care has been successfully incorporated into health care clinician curriculum and professional practice models [97,98], showing improvement in health care delivery [41,99,100].…”
Section: Implications For Practice Policy and Professional Developmentmentioning
confidence: 99%
“…Implementation or enculturation of the components of a PPM create a practice environment that supports nurses' control over their practice and enhances patient care quality 2,26. For the model to be useful, however, continuous monitoring and assessment of its relevance are necessary 24,33,40–44. In 2012, Berger and colleagues26 reported that Norton Healthcare had been implementing their practice model for nearly 2 years and was continuing to re-evaluate it through adoption and modification.…”
Section: Discussionmentioning
confidence: 99%
“…2,26 For the model to be useful, however, continuous monitoring and assessment of its relevance are necessary. 24,33,[40][41][42][43][44] In 2012, Berger and colleagues 26 reported that Norton Healthcare had been implementing their practice model for nearly 2 years and was continuing to re-evaluate it through adoption and modification. Similarly, organizations advancing a PPM must recognize that the PPM is not a static, permanent model, but one that will need to adapt and change as the organization transforms over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of research on the relationship between nursing staff and patients, and the correlation between nursing care satisfaction and relational care. An extensive literature search revealed a scarcity of research on the above topics at present and most were single-center studies with small sample sizes (13)(14)(15). Acknowledging the above, numerous humanistic nursing training programs have gradually been carried out in China.…”
Section: Introductionmentioning
confidence: 99%